Модель розвитку газової галузі за невизначеної інформації щодо перспектив розробки ресурсів і запасів природного газу в Україні - Kaplin M.I.; Bilan T.R.; Makarov V.M.; Perov M.O. (General Energy Institute of the National Academy of Sciences of Ukraine, 2020)
We propose a model of calculating the development of gas industry to solve the problem of choosing options for commissioning new natural gas fields and intensifying the existing fields. The model is based on representing development options with achievable volumes of the increase in annual production in the problem of integer linear programming. New and operating natural gas fields can be presented in the model by statistical information on their distribution by reserves and depths of occurrence with the corresponding development costs, as well as the dependences of the predicted volume of annual production from the taken measures and technologies to improve the efficiency of gas extraction.Model calculations provide a two-stage method for determining the options for development of the industry. At the first stage, a variety of options is optimized according to the criterion of specific expenses per 1000 m3 of gas produced during the entire program period. The second stage ensures the optimal distribution of selected options between the periods of program using the criterion of production volume and with the limited costs of previous period for the preparation, prospecting, and exploration of deposits.We present the results of calculating feasible options of the development of gas production industry based on statistical information on volume, mining-and-geological and cost indicators of the development of resources and natural gas reserves. Based on calculations, we investigated the options of uniform distribution of investment, as well as their growth from the first stage to the next ones. For both cases, the priority is set for the selection of fields with greater reserves at the same depths of occurrence. Such a procedure for putting fields into operation is expedient, both from the viewpoint of criterion for the optimal functioning of the industry over a long period of time – the specific costs of production, and on the basis of considerations of achieving the highest volumes of extraction during the shortest possible time. In the case of small capital investments in the development of industry, the model selects small-volume reserves of deposits according to the structure of Ukrainian reserves.